Pengaruh Variasi Jenis Pakan Terhadap Laju Pertumbuhan Berat Ikan Mas (Cyprinus carpio) dalam Sistem Akuakultur - Dimas Ardiansyah; Intan Permatasari (Insight of Biology, 2025)
This study aims to evaluate the effect of different feed types on the growth rate, feed efficiency, and survival rate of common carp (Cyprinus carpio) in an aquaculture system. The experiment was conducted for 60 days using a completely randomized design with four feed treatments: commercial feed, plant-based feed, animal-based feed, and a combination of plant- and animal-based feeds, each with three replications. Growth performance was assessed by measuring weight gain, specific growth rate (SGR), feed conversion ratio (FCR), and survival rate (SR). The results showed that the combination feed produced the highest growth rate, with an average final weight of 60 g, SGR of 3.52%/day, FCR of 1.05, and 100% survival rate. The animal-based feed also showed good performance, while the plant-based feed resulted in the lowest growth and feed efficiency. Statistical analysis revealed significant differences (p<0.05) among the treatments. The study concludes that the combined plant-animal feed provides a balanced nutritional profile that optimizes growth performance and feed efficiency in common carp culture, making it a recommended feed formulation for aquaculture practices.